Reassessing Women's Obligation in Friday Prayer on Fiqh al-Ḥadīth and Maqāṣid al-Sharīʿah in the Perspective of Majelis Tafsir Al-Qur'an (MTA) - Sukron, Mokhamad; Said Agil Husin Al-Munawar; Zaitunah Subhan; Supriyanto (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
This study investigates the interpretation of the Majelis Tafsir Al-Qur'an (MTA) regarding the obligation of Friday prayers for women, employing the analytical frameworks of Fiqh al-Ḥadīth and Maqāṣid al-Sharīʿah. MTA adopts a literal exegesis of QS. al-Jumuʿah: 9, asserting its universal applicability irrespective of gender. The study critically reevaluates the traditionally understood Hadiths to exempt women, interpreting them as providing legal flexibility rather than categorical exclusion. By applying sanad (chain of transmission) and matan (text-content) analysis, MTA integrates classical methodological rigor with contextual reasoning, thereby advocating a reformist yet tradition-conscious stance. This research highlights MTA's inclusive perspective as a significant contribution to contemporary Islamic legal discourse, aiming to promote enhanced religious participation and social cohesion. Nonetheless, the study identifies ongoing challenges, including contextual limitations and restricted mosque access for women. The findings underscore how MTA's interpretive model embodies a progressive rethinking of Islamic obligations in response to evolving social realities.